Social And Cultural Predictors Of Tattooing Among Athletes Of Federal Universities In Nigeria - Ekenedo, Golda; Elechi, Stella (Advances in Social Sciences Research Journal, 2020)
The cross-sectional study investigated the social and cultural predictors of tattooing among athletes of Federal Universities in Nigeria. Data was collected from a sample of 594 athletes using a validated structured questionnaire with a reliability index of 0.77. . Data collected were analysed using the Statistical Package for Social Sciences (SPSS) version 21. Multiple regression and logistic regression were used to establish the joint and independent predictors of tattooing among the athletes. The findings of the study revealed that peer influence (P=0.003), family influence (P=0.000), personal achievement (P=0.006) and academic background (P=0.000) were significant social predictors of tattooing among the athletes. Traditional (P=0.000) and religious beliefs (P=0.000) were also found to be significant cultural predictors of tattooing among the athletes. It was concluded based on the findings that the practice of tattooing among Nigerian University athletes followed similar social influence pattern as in other parts of the world. Social marketing was recommended as a veritable tool for health education and communication to enhance informed decisions regarding tattooing among the athletes.